Prognostic value of the total cosine R to T measured in high resolution body surface potential mapping during exercise test. (July 2015) - Kania, Michał; Maniewski, Roman; Kobylecka, Małgorzata; Zaczek, Rajmund; Królicki, Leszek; Opolski, Grzegorz; Janusek, Dariusz
Highlights: The aim was to assess the prognostic value of the total cosine R-to-T. The HRBSPM were recorded during exercise test in the group of 123 subjects. TCRT measured at peak exercise might be an effective predictor of arrhythmia. Analysis during exercise improves sensitivity compared to measurement at rest. TCRT parameter normalization to heart rate increases diagnostic value. Abstract: Background : The total cosine R-to-T (TCRT) is a vectorcardiographic measure of differences in propagation of depolarization and repolarization in the heart. The high TCRT value reflects increased heterogeneity of repolarization process. The aim of study was to assess the prognostic value of the TCRT measured during exercise stress test. Methods : The high-resolution body surface potential maps were recorded at rest and during exercise test in the group of 90 cardiac patients and 33 healthy volunteers. The TCRT was computed from averaged in time ECG signals. The prognostic value of TCRT parameter was determined based on the results of SPECT and echocardiography. Results : TCRT was heart rate dependent and its magnitude decreased when measured at peak exercise in comparison to TCRT measured at rest. The significant differences in TCRT were obtained between patients with low (LVEF ≤ 40%, ) and high (LVEF > 40%) left ventricular ejection fraction. These differences were greater if the TCRT was determined from a 67-lead ECG than computed from the standard ECG leads and were more pronounced for TCRT determined at peak exercise than at rest. The separation capacity was farther improved for TCRT normalized to mean heart rate. Simulation and experimental results showed that presence and localization of myocardial ischemia or post-infarction scar tissue have negligible impact on TCRT. Conclusions : Wider R-to-T angle was associated with lower LVEF. The statistically significant differences of TCRT in patients with low LVEF and high LVEF may suggest high prognostic value of TCRT parameter in risk assessment of ventricular arrhythmia.